أثر حصول المؤسسة على شهادة الجودة أيزو 9001 في تحقيق الميزة التنافسية دراسة ميدانية شركة روائح الورود لصناعة العطور بالوادي - عبد الحميد, الأخضري; حاج الطيب, بالهادف; معمر, حميد (جامعة الوادي - University of Eloued, 2023)
يتمحور هدف هذه الدراسة ، إلى إبراز أثر حصول المؤسسة على شهادة الجودة ( 9001 ISO ) في تحقيق الميزة التنافسية من خلال دراسة علاقة بين إدارة الجودة ايزو 9001 بمبادئها (القيادة ، اتخاذ القرارات المبنية على الأدلة ، منهجية العمليات ، مشاركة العاملين، إدارة العلاقات ، التركيز على العميل،و التحسين المستمر)، والميزة التنافسية بأبعادها ( التكلفة ، الجودة ، المرونة ، الإبداع و التسليم ) بشركة الورود لصناعة العطور بالوادي، ولتحقيق أهداف هذه المذكرة قام الطلبة بتصميم استبانة ،وتم توزيع 112 استبانة على عمال المؤسسة محل الدراسة، تم استرجاع منها 67 استبانة قابلة للمعالجة ، وتم معالجة البيانات باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية ( SPSS )، كما توصلت الدراسة الى جملة من النتائج من أهمها يوجد أثـر ارتباط قوية إيجابية وأثر ذو دلالة إحصائية لتطبيق مبادئ إدارة الجودة ايزو 9001 في تحقيق في تحقيق الميزة التنافسية في المؤسسة محل الدراسة ،حيث أن تطبيق مبادئ إدارة الجودة ايزو9001 يفسر ما قيمته (53.1) من التغير الحاصل في الميزة التنافسية، وقد أوصت الدراسة بضرورة الاستمرار في دعم تطبيق مبادئ إدارة الجودة ايزو 9001 والمحافظة على الأسبقيات التنافسية المكتسبة The objective of this study is to highlight the impact of obtaining the ISO 9001 quality certificate in achieving competitive advantage by studying the relationship between ISO 9001 quality management and its principles (leadership, evidence-based decision-making, process methodology, employee participation, relationship management, focus on the customer, and continuous improvement), and the competitive advantage in its dimensions (cost, quality, flexibility, creativity and delivery), In Al-wourood Company for the manufacture of perfumes in El-oued, and to achieve the objectives of this memorandum, the students designed a questionnaire, and 112 questionnaires were distributed to the workers of the institution under study, of which 67 questionnaires could be processed, and the data was processed using the Statistical Packages for Social Sciences (SPSS) program. Among the results, the most important of which is that there is a strong positive correlation and a statistically significant effect of the application of the principles of quality management ISO 9001 in achieving the competitive advantage in the institution under study, as the application of the principles of quality management ISO 9001 explains the value of (53.1%) of the change in the competitive advantage The study recommended the need to continue to support the implementation of the principles of quality management ISO 9001 and to maintain the acquired competitive priorities .
Keywords: الجودة ، إدارة الجودة : شهادة الأيزو9001 ، التنافسية ، الميزة التنافسية; quality, quality management: ISO 9001 certification, competitiveness , competitive advantage.